ChemInform Abstract: Palladium‐Catalyzed Enolate Arylation as a Key C—C Bond‐Forming Reaction for the Synthesis of Isoquinolines. Issue 20 (April 2016) - Pilgrim, Ben S.; Gatland, Alice E.; Esteves, Carlos H. A.; McTernan, Charlie T.; Jones, Geraint R.; Tatton, Matthew R.; Procopiou, Panayiotis A.; Donohoe, Timothy J.
Abstract: The Pd‐catalyzed enolate arylation leads to ketones (III), which are cyclized with NH4 Cl to afford desired isoquinolines (IV).